Anti-tumor efficacy of anti-GD2 CAR NK-92 cells in diffuse intrinsic pontine gliomas - Zuo, Pengcheng; Li, Yaopeng; He, Chi; Wang, Tantan; Zheng, Xu; Liu, Hao; Wu, Zhen; Zhang, Junting; Liao, Xuebin; Zhang, Liwei (Frontiers in Immunology, 2023)
Background Diffuse intrinsic pontine gliomas (DIPGs) are rare and fatal pediatric brainstem gliomas with no cure. Chimeric antigen receptor (CAR)-engineered natural killer (NK) cells have been proven effective in treating glioblastoma (GBM) in preclinical studies. However, there are no relevant studies on the CAR-NK treatment for DIPG. Our study is the first to evaluate the anti-tumor activity and safety of GD2-CAR NK-92 cells treatment for DIPG. Methods Five patient-derived DIPG cells and primary pontine neural progenitor cell (PPC) were used to access disialoganglioside GD2 expression. Cell killing activity of GD2-CAR NK-92 cells was analyzed by in vitro cytotoxicity assays. Two DIPG patient-derived xenograft models were established to detect the anti-tumor efficacy of GD2-CAR NK-92 cells in vivo. Results Among the five patient-derived DIPG cells, four had high GD2 expression, and one had low GD2 expression. In in vitro assays, GD2-CAR NK-92 cells could effectively kill DIPG cells with high GD2 expression while having limited activity against DIPG cells with low GD2 expression. In in vivo assays, GD2-CAR NK-92 cells could inhibit tumor growth in TT150630 DIPG patient-derived xenograft mice (high GD2 expression) and prolong the overall survival of the mice. However, GD2-CAR NK-92 showed limited anti-tumor activity for TT190326DIPG patient-derived xenograft mice (low GD2 expression). Conclusion Our study demonstrates the potential and safety of GD2-CAR NK-92 cells for adoptive immunotherapy of DIPG. The safety and anti-tumor effect of this therapy need to be further demonstrated in future clinical trials.